2015
DOI: 10.7567/jjap.54.021302
|View full text |Cite
|
Sign up to set email alerts
|

Highly oriented lateral growth of SiGe thin films on glass induced by constitutional undercooling

Abstract: Enhanced lateral growth of semiconductor thin films on glass was investigated. The unidirectional growth of silicon (Si) was achieved by introducing continuous-wave laser lateral crystallization. Alloying germanium (Ge) with Si led to highly oriented lateral growth (HOLG) of SiGe thin films. The HOLG and Ge segregation in these films were explained by the constitutional undercooling model. Quasi-single crystals were grown when the Ge mole fraction was 0.3. Using a single scan of the laser on SiGe causes the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This study aims to understand the performance of CLC poly-Si1-xGex TFTs and highlight the issues pertaining to CLC poly-Si1-xGex thin films by comparing the performance of CLC poly-Si1-xGex TFTs with that of CLC poly-Si TFTs. Part of this study has been reported previously (14)(15)(16)(17)(18)(19)(20). This study presents new data pertaining to crystalline properties of CLC poly-Si1-xGex thin films and performance of pch CLC poly-Si and poly-Si1-xGex TFTs.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…This study aims to understand the performance of CLC poly-Si1-xGex TFTs and highlight the issues pertaining to CLC poly-Si1-xGex thin films by comparing the performance of CLC poly-Si1-xGex TFTs with that of CLC poly-Si TFTs. Part of this study has been reported previously (14)(15)(16)(17)(18)(19)(20). This study presents new data pertaining to crystalline properties of CLC poly-Si1-xGex thin films and performance of pch CLC poly-Si and poly-Si1-xGex TFTs.…”
Section: Introductionmentioning
confidence: 61%
“…The variation in the intensity of the Raman peak is caused by the surface roughness (21). The crystalline quality and grain sizes of the CLC poly-Si and poly-Si1-xGex films with x=0.05, 0.1, and 0.3 were intensively examined using FE-SEM, EBSD and Raman scattering (15,(17)(18)(19)(20). The grain length of poly-Si1-xGex increased with increasing Ge concentration.…”
Section: Crystalline Quality Of Clc Poly-si1-xgex Thin Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…[99] In particular, excimer laser annealing (ELA) has been used to crystallize large areas of a-Si films deposited on glass substrates, leading to the fabrication of low-cost activematrix-driven flat panel displays. [100] A wide range of laser sources operating at UV, visible, and NIR wavelengths, in pulsed and CW modes, has been exploited to crystallize group IV semiconductors, including Si, [101] Ge, [102] SiGe, [103] and GeSn [104,105] thin films and components. These materials have been deposited on both crystalline (i.e., bulk Si) and insulator substrates, which can be further exploited to alter the crystallization process.…”
Section: Laser Annealing Crystallization and Reflowing Of Semiconductors On Planar Substrates For Fabrication Of Optical Waveguidesmentioning
confidence: 99%
“…A wide range of laser sources operating at UV, visible, and NIR wavelengths, in pulsed and CW modes, has been exploited to crystallize group IV semiconductors, including Si, [ 101 ] Ge, [ 102 ] SiGe, [ 103 ] and GeSn [ 104,105 ] thin films and components. These materials have been deposited on both crystalline (i.e., bulk Si) and insulator substrates, which can be further exploited to alter the crystallization process.…”
Section: Laser‐processed Planar Photonic Devicesmentioning
confidence: 99%